Photovoltaic system under uneven light condition and variable load with modified incremental resistance algorithm - S, Sreekanth; X. Felix Joseph, Dr (International Journal of Engineering and Technology, 2018)
On scrutinizing Power vs. Voltage curves of P_V arrays which receives non-uniform insolation of light or simply during uneven lighting conditions (ULCs) multiple LMPPTs are exhibited. Conventional MPPT methods are efficient under normal conditions even though they failed to identify the GMPPTs from LMPPTs under ULCs. To improve the productivity of Maximum power point tracking method for P_V arrays under both ULCs and normal conditions some modifications are tried in this paper. The Incremental-resistance method added with some alterations enables to track the LMPPTs as well as GMPPTs very effectively and accurately with fewer numbers of steps. In proposed system losses during GMPP, tracking is minimized under ULCs. Simulation is performed in Mat lab.Â Â Â